Marie Curie [videorecording (DVD)] : the courage of knowledge - Noëlle, Marie; Noëlle, Marie; Gruszka, Karolina, 1980-; Worthalter, Arieh; Berling, Charles (Big World Pictures, 2018)
Physicist, chemist, and pioneer in the study of radioactivity, Marie Sklodowski Curie spent her life setting precedents. She was the first woman to win the Nobel Prize and the first person to win it twice. As the first female professor at the University of Paris, she had to overcome the condescension and antagonism of France's male-dominated academic establishment. She also courted controversy of the sort that still threatens to quash the careers of public figures today.